3D Polyoxometalate-Functionalized Graphene Quantum Dots with Mono-Metallic and Bi-Metallic Nanoparticles for Application in Direct Methanol Fuel Cells. Issue 10 (1st January 2016) - Tolga Çolak, Alper; Eren, Tanju; Yola, Mehmet Lütfi; Beşli, Erdem; Şahin, Onur; Atar, Necip
Abstract : A fuel cell is an electrochemical cell that converts a source fuel into an electrical current. It generates electricity inside a cell through reactions between a fuel and an oxidant, triggered in the presence of an electrolyte. Fuel cells have been attracting more and more attention in recent decades due to high-energy demands, fossil fuel depletions, and environmental pollution throughout world. A facile and cost-effective catalysts have been developed on polyoxometalate (NaPWO) functionalized graphene quantum dots (GQDs) with several mono-metallic and bi-metallic nanoparticles such as platinum nanoparticles (PtNPs), palladium nanoparticles (PdNPs) and platinum-palladium nanoparticles (Pt-PdNPs). The successful synthesis of nanomaterials and the prepared glassy carbon electrode (GCE) surfaces were confirmed by transmission electron microscope (TEM), X-ray photo electron spectroscopy (XPS), scanning electron microscope (SEM), electrochemical impedance spectroscopy (EIS) and X-ray diffraction (XRD) method. According to TEM images, the average particle sizes of PtNPs and PdNPs were found to be approximately 20–30 nm. The Pt-PdNPs/NaPWO/GQDs also exhibited a higher peak current for methanol oxidation than those of comparable PdNPs/NaPWO/GQDs and PtNPs/NaPWO/GQDs, thus providing evidence for its higher electro-catalytic activity.